2022
DOI: 10.1002/vetr.1795
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic sexing in turtles and tortoises: 467 cases (2007–2017)

Abstract: Background This multi‐institutional retrospective study evaluated the feasibility and safety of endoscopic sex identification in 467 turtles and tortoises, representing 10 species. Methods Medical records of turtles and tortoises that underwent endoscopic sex identification at the University of Georgia, New England Aquarium and Turtle Conservancy were reviewed for presurgical management, anaesthesia, endoscopic equipment and surgical techniques, endoscopic results and complications. Results The majority of ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Coelioscopy has proven to be a safe and accurate method for identifying sex in a large number of chelonians of different species 32 . Previous studies have demonstrated that injectable anesthetic agents alone may be insufficient and that the addition of local lidocaine improves anesthesia overall 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coelioscopy has proven to be a safe and accurate method for identifying sex in a large number of chelonians of different species 32 . Previous studies have demonstrated that injectable anesthetic agents alone may be insufficient and that the addition of local lidocaine improves anesthesia overall 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the stage at which gonads can be reliably identified is consistent within a species, but can be variable between species. For example, the Chinese box turtle ( Cuora flavomarginata ) exhibits obvious gonadal dimorphism at hatching and can be reliably sexed as soon as the yolk sac has been absorbed at about four months and 35 g bodyweight; however, the gonads of radiated tortoises ( Astrochelys radiata ) become difficult to differentiate below about nine months or 100 g body weight 32 , 33 . To mitigate such risks, it is therefore wise to start with the largest animals in the cohort, and progress to the smaller animals until safety margins or certainty of gonadal identification decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation